Pan-african education - Marah, John Karefah (London (UK): Routledge, 2018)
"This book makes a critical contribution to the study of pan-Africanism and the education of African people for continental African citizenship. It is a unique endeavor in that it intersects the social history of pan-Africanism and the education of African people at a 'global' level and provides reflections from a multidisciplinary perspective on the urgency for continental pan-Africanism educational system in ordifer to produce a more renascent African for the twenty-first century.Arguing that Pan-African Education is a mass-based educational system that will 'craft' a pan-African African personality, John Marah calls for integrated African school systems and curriculum changes conducive to larger social integration and institutionalized pan-African educational processes. The establishments of pan-African Teachers Colleges; intensive language institutes; pan-African literature courses; the training of African military and police forces; the use of music, sports, media and other extra-curricular activities (the hidden curriculum), etc.; are viewed as essential aspects in the socialization of a pan-African character or personality.Pan-African Education is an essential read for students and scholars of Pan-Africanism, African and Africana Studies, and Black Studies."--Provided by publisher.
Chapter 1 An introduction to pan-African education -- chapter 2 The virtues and challenges in traditional African education -- chapter 3 From the temples of Egypt to colonial education in Africa -- chapter 4 African nationalists on African education -- chapter 5 Educational adaptation and pan-Africanism: developmental trends in Africa -- chapter 6 America and Africa: a comparative study in educational philosophy -- chapter 7 Images of colonial and post-colonial Africa without African unity -- chapter 8 The saliency of pan-African education -- chapter 9 From Toussaint L{u2019}Ouverture to President Kwame Nkrumah: a discourse on a pan-African vision -- chapter 10 Reflections on pan-African education and pan-Africanism.
Includes bibliographical references and index.
Keywords: Education -- Africa -- History; Pan-Africanism.; z; Panafricanisme; Education; Pan-Africanism; Africa; History